2007
DOI: 10.1159/000106510
|View full text |Cite
|
Sign up to set email alerts
|

Intersegmental Arterial Communication between the Medial and Left Lateral Segments of the Liver

Abstract: Background/Aims: Although the interlobar arterial collateral of the liver has been thoroughly analyzed, few reports have described the intersegmental arterial collateral between the medial and left lateral segments. Methods: The hepatic arterial system of the left liver was evaluated using 12 latex resin cast specimens in which latex resin was injected into the left hepatic artery after ligation of the right hepatic artery. Results: In all 12 livers, an intersegmental collateral between the medial and left lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…There is a possibility that liver infarction and/or biliary complication will result if the blood flow is sparse [4]. A communicating arcade is also present between the lateral and medial segments of the liver [5]. Despite the use of the severed MHA for RHA reconstruction in Case 1 in the present study, the postoperative course was found to be uneventful.…”
Section: Discussionmentioning
confidence: 73%
“…There is a possibility that liver infarction and/or biliary complication will result if the blood flow is sparse [4]. A communicating arcade is also present between the lateral and medial segments of the liver [5]. Despite the use of the severed MHA for RHA reconstruction in Case 1 in the present study, the postoperative course was found to be uneventful.…”
Section: Discussionmentioning
confidence: 73%
“…Numerous corrosion cast studies which formed the basis of our monograph on the hilar plate anatomy clearly show a well-defined rich hilar plate plexus with vigorous supply from the rex recess and reinforced by several feeder vessels originating from named graft arteries 1-1.5 cm proximal to the hilar plate [5]. Therefore, we believe that dividing the artery flush with the graft or a diathermy burn close to the hilar plate is more likely to compromise the hilar plexus and risk BC than the absolute length of the bile duct.…”
Section: Dear Editormentioning
confidence: 77%
“…This way, a single administration was possible from the RHA. C, D SPECT and 90Y-PET/CT images showed homogeneous perfusion within the redistributed liver area trunks, such as the SMA or LGA [18,26]. In these cases, numerous enteric branches may be located in proximity to the origin of the hepatic branches, and even a small amount of reflux might result in complications.…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have demonstrated that arterial collaterals establish liver arterial connections between segments or lobes [18][19][20]. These reports have been the basis for vascular redistribution, which has routinely been performed for years in cases of liver tumors treated with intraarterial chemotherapeutic infusion [21,22].…”
Section: Discussionmentioning
confidence: 99%